Total HIP arthroplasty in patients with Parkinson's disease - Mathew, Pradeep George; Sponer, Pavel; Kucera, Tomás; Grinac, Michal; Knízek, Jirí (Acta medica (Hradec Kralove), 2013)
The aim of this study is to evaluate the results of total hip arthroplasty in patients with Parkinson's disease during a period of five years, focusing on the assessment of the risks and benefits of surgery. During this period we performed total hip arthroplasty in 14 patients (15 hips) with Parkinson's disease. Patients were evaluated by subjective symptoms and objective findings, with a focus on the use of support while walking and walking distance, severity of Parkinson's disease before surgery and at the time of the last follow-up. During the postoperative period, the following parameters were assessed: length of ICU stay, mobilization, complications, the total duration of hospitalization and follow-up care after discharge. Of the 11 patients (12 hips) followed-up 1-5 years with an average of 3 years after operation 8 cases showed progression of neurological disability. 5 patients (6 hips) showed an increased dependence on the use of support when walking and reduced distance that the patient was able to walk. Subjectively, 10 hip joints were completely painless and 2 patients complained of only occasional mild pain in the operated hip. Complications that were encountered were urinary tract infection (5 patients), cognitive impairment (3 patients) and pressure ulcer (2 patients). We did not observe any infection or dislocation of the prosthesis. Three patients fell and fractured the femur and 3 patients in our cohort died during follow up. Implantation of total replacement is possible with judicious indication after careful evaluation of neurological finding in patients with minimal or mild functional impairment of the locomotor system. Prerequisite for a good result is precise surgical technique and optimal implant position with balanced tension of the muscles and other soft tissues around the hip.
Keywords: senioři; náhrada kyčelního kloubu; senioři nad 80 let; reoperace; Arthroplasty, Replacement, Hip; Cohort Studies; výsledek terapie; mužské pohlaví; periprotetické fraktury; selhání protézy; kohortové studie; Reoperation; Aged, 80 and over; Parkinsonova nemoc; Hip Fractures; ženské pohlaví; Humans; Periprosthetic Fractures; Parkinson Disease; Femur Head Necrosis; nekróza hlavice femuru; fraktury kyčle; Female; Aged; Treatment Outcome; Prosthesis Failure; lidé; Male